Long-Term Cardiac Safety and Survival Outcomes of Neoadjuvant Pegylated Liposomal Doxorubicin in Elderly Patients or Prone to Cardiotoxicity and Triple Negative Breast Cancer. Final Results of the Multicentre Phase II CAPRICE Study - Gil-Gil, Miguel J.; Bellet, Meritxell; Bergamino, Milana; Morales, Serafín; Barnadas, Agustí; Manso, Luís; Saura, Cristina; Fernández-Ortega, Adela; Garcia-Martinez, Elena; Martinez-Jañez, Noelia; Melé, Mireia; Villagrasa, Patricia; et al. (Frontiers in Oncology, 2021)
Background: The CAPRICE trial was designed to specifically evaluate neoadjuvant pegylated liposomal doxorubicin (PLD) in elderly patients or in those with other cardiovascular risk factors in whom conventional doxorubicin was contraindicated. The primary analysis of the study showed a pathological complete response (pCR) of 32% and no significant decreases in LVEF during chemotherapy. Here, we report important secondary study objectives: 5-year cardiac safety, disease-free survival (DFS), overall survival (OS) and breast cancer specific survival (BCSS). Methods: In this multicentre, single-arm, phase II trial, elderly patients or those prone to cardiotoxicity and high risk stage II-IIIB breast cancer received PLD (35 mg/m2) plus cyclophosphamide (600 mg/m2) every 4 weeks for 4 cycles, followed by paclitaxel for 12 weeks as neoadjuvant chemotherapy (NAC). Left ventricular ejection fraction (LVEF) monitorization, electrocardiograms and cardiac questionnaires were performed at baseline, during treatment and at 9, 16, 28 and 40 weeks thereafter. The primary endpoint was pCR and 5-year cardiac safety, DFS, BCSS and OS were also analyzed. Results: Between Oct 2007, and Jun 2010, 50 eligible patients were included. Median age was 73 (35-84) years, 84% were older than 65; 64% of patients suffered from hypertension, and 10% had prior cardiac disease. Most of tumors (96%) were triple negative. No significant decreases in LVEF were observed. The mean baseline LVEF was 66.6% (52-86) and after a median follow-up of 5 years, mean LVEF was 66 (54.5-73). For intention to treat population, 5-year DFS was 50% (95% CI 40.2-68.1) and 5-year OS was 56% (95%CI 41.2-68.4). There were 8 non-cancer related deaths, achieving a 5 years BCSS of 67.74% (CI 95%:54.31%- 81.18%). In conclusion: At 5-year follow-up, this PLD-based NAC regimen continued to be cardiac-safe and effective in a population of very high-risk breast cancer patients. This scheme should be considered as an option in elderly patients or in those with other risks of developing cardiotoxicity.